Teaching for understanding : linking research with practice - 4 0 16; Wiske, Martha Stone; 5 (San Francisco : Jossey-Bass Publishers, 1998)
Describes the method of teaching for understanding and explains how teachers can use it to increase their students' ability to develop a level of understanding that will serve them throughout their lives.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; Teaching for Understanding Project.;Teaching for Understanding Project. -- 6; Aims and objectives. -- Teaching.;Learning, Psychology of.;Education;Psychology of learning; 20; 2